Enhanced recovery after surgery in paediatric patients undergoing gastrointestinal surgeries - A scoping review, - Wai Tak Victor Li; Wan Kei Li; Yat Chi Chan; Tsz Yan Cheung; Clarice Kai-ying Su; Qian Xiu Rosemond Tan; Shun Lok Wong; Tsz Ho Wong; Patrick Ho Yu Chung (Elsevier, 2023)
Objective: Implementing Enhanced Recovery After Surgery (ERAS) protocols has been shown to improve perioperative outcomes in adults undergoing gastrointestinal surgeries. Herewith, we performed a scoping review to evaluate the practice of ERAS protocol in paediatric patients undergoing gastrointestinal surgeries. Methodology: PubMed, Medline (Ovid), Scopus, and Cochrane Library were searched. Studies investigating the effect of adopting an ERAS protocol on children undergoing gastrointestinal surgeries are included. Data on the study design, operative procedures, ERAS element, and surgical outcomes were evaluated. Elements of ERAS were also examined. Results: among the 15 included papers, patients under an ERAS protocol have shorter length of stay (n = 11); better postoperative gastrointestinal function in terms of time to any (n = 5) or regular amount of diet (n = 5), shorter time to first defaecation (n = 4), and less requirement of parenteral nutrition (n = 2); and less opioid use in the intraoperative (n = 4) and postoperative (n = 5) periods. An average of 9.67 ERAS elements are adopted in the studies with the commonest being providing information and education to the patient and family (n = 12). Conclusion: ERAS protocols have apparent benefits for children undergoing gastrointestinal surgeries with improved perioperative outcomes. Evidence from higher quality study is warranted to confirm this relationship in detail and to enhance the applicability. Level of evidence: This is a review study, hence not applicable